Sedimentology of the Dezadeash flysch and its implications for strike-slip faulting along the Denali Fault, Yukon Territory and Alaska - Eisbacher, G. H. (Canadian Journal of Earth Sciences, 1976)
The Dezadeash Formation of Late Jurassic – Early Cretaceous age is a flysch sequence with a thickness of about 3000 m. It consists of turbidites, mass-flow deposits, and argillite. Most of the formation was deposited on a deep-sea fan system fed by an uplifted volcanogenic terrane to the west. Along its western border, the Dezadeash flysch is truncated by the Denali Fault; towards the east, part of the Dezadeash Formation seems to have been metamorphosed into the Kluane Schist.It is suggested that both the Dezadeash flysch and Kluane Schist have been torn apart by the Denali Fault and that equivalent rock units are found within the Nutzotin Mountains Sequence and the McLaren Metamorphic Belt of Alaska. A dextral displacement of 300 km could account for the present distribution of these units along the Denali Fault. This offset was probably achieved during mid-Tertiary time.